Pendidikan Syair pada Masa Pra Islam - Abdullah Abdullah (Fakultas Adab dan Humaniora, UIN Syarif Hidayatullah Jakarta, Indonesia, 2010)
This paper seeks to answer what is a harsh and isolated environment? How education can last poem in harsh environments and isolated in the preIslamic? How can the educational process take place? Through a social-historical approach to uncover the origins and development of literature in the Arabic world particularly with poetry education, it is found that the process of learning takes place in the context of Arabic poetry community needs. It is understood that the pre-Islamic poetry education received full support from the tribes since its benefits would be felt directly by the tribes who were the most prominent part of the poetry educational process. Tribes contributed a great share given in the form of provision to create a conducive environment for poetry in a practical implementation of education. The urgency and significance of this paper in the context of .literary learning in the Department of Arabic Language and Literature UIN Syarif Hidayatullah Jakarta can be an alternative for the development and application of literary learning that match the needs of students.